Heart failure with preserved ejection fraction and atrial fibrillation: clinical management in the context of recent therapeutic advances in heart failure and electrophysiology - Yang, Eunice; Rashid, Haroon (Frontiers in Cardiovascular Medicine, 2024)
Heart failure with preserved ejection fraction (HFpEF) and atrial fibrillation (AF) have emerged as major age-related epidemics within cardiology. Both conditions carry overlapping symptomatology, and delineating between AF and HFpEF from a diagnostic standpoint is challenging as echocardiographic and biomarker assessments used to diagnose HFpEF may be impacted by AF. Indeed, these two conditions are commonly found in the same individual, so much so that AF has been used in proposed diagnostic criteria for HFpEF. The frequent concomitant presence of these two conditions is associated with poorer quality of life, exertional capacity, as well as increased risk for decompensated heart failure and all-cause mortality. Though these deleterious effects of AF in HFpEF patients are well described, we currently have only a superficial understanding of the complex interplay between these two conditions. Preliminary studies on intervening in AF in HFpEF are very small, with mixed data on whether modifying the natural history of AF can lead to improvement in heart failure (HF) outcomes in HFpEF. In this review, we will describe the clinical implications of carrying both cardiovascular conditions, address recent advances in HFpEF and AF, and highlight preliminary studies targeted at reduction of effects associated with AF burden in HFpEF.